Mapping of urban garden soil microbiomes in Bangladesh - Hoque, M. Nazmul; Rana, Md. Liton; Gilman, Md. Abu Ahsan; Pramanik, Pritom Kumar; Islam, Md. Saiful; Punom, Sadia Afrin; Hassan, Jayedul; Islam, Tofazzal; Ramasamy, Srinivasan; Schreinemachers, Pepijn; Oliva, Ricardo; Rahman, Md. Tanvir (American Society for Microbiology, 2025)
Shotgun metagenomics revealed distinct microbiome profiles in the garden soils of Dhaka and Gazipur district, Bangladesh, with Bacillus spp. demonstrating ecological dominance (>53% relative abundance) and location-specific distribution patterns. These findings highlight Bacillus species as prevalent microbes in urban garden soils.